2018
DOI: 10.1007/s10995-018-2452-y
|View full text |Cite
|
Sign up to set email alerts
|

Motivating Smoking Cessation Text Messages: Perspectives from Pregnant Smokers

Abstract: Allowing pregnant smokers to write cessation text-messages for other pregnant women can provide relevant insight into intervention content. Specifically, pregnant smokers appear to equally promote gain and loss frames, but may prefer messages that include components of fear and guilt related to the impact of smoking on their baby. Additional research is needed to systematically uncover perspectives of pregnant smokers to ensure interventions are optimally effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…Las mujeres y parejas expresan su preferencia por información no focalizada en aspectos negativos del consumo. En contraposición, otros estudios cualitativos muestran que las embarazadas consideran que el miedo y la culpa por los daños al bebé relacionados con fumar pueden ser especialmente influyentes para la cesación 21 .…”
Section: Discussionunclassified
“…Las mujeres y parejas expresan su preferencia por información no focalizada en aspectos negativos del consumo. En contraposición, otros estudios cualitativos muestran que las embarazadas consideran que el miedo y la culpa por los daños al bebé relacionados con fumar pueden ser especialmente influyentes para la cesación 21 .…”
Section: Discussionunclassified
“…In previous studies, text messages have been shown to increase the health knowledge of pregnant women (19), to encourage smoking cessation or reduction in pregnant women (20), to encourage breastfeeding (21), and to develop a positive attitude toward vaccination (22). Also, in meta-analysis and systematic review studies, it has been stated that text messages increase the number of prenatal care visits of pregnant women and is an effective tool in pregnancy education (23,24).…”
Section: Discussionmentioning
confidence: 99%